1983
DOI: 10.1007/bf00973158
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic determination of renal volumes in normal neonates

Abstract: Renal diseases that affect renal size without altering renal architecture require a quantitative means of detection. A prospective study was undertaken to establish normal values for renal volumes in healthy neonates using sonography. Volumes were determined by two methods; (1) the serial area-volume method using parallel transverse images; and (2) the prolate ellipsoid model of the kidney using orthogonal diameters taken from ultrasound images. Renal volumes for both the right and left kidneys in both sexes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
1
3

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 12 publications
5
25
1
3
Order By: Relevance
“…Some of these studies used the child's age for standardizing kidney length [2,3]. As recognized in the literature and corroborated by our study, better predictions of renal length have been obtained with a body measurement such as height, weight, or surface area [4].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Some of these studies used the child's age for standardizing kidney length [2,3]. As recognized in the literature and corroborated by our study, better predictions of renal length have been obtained with a body measurement such as height, weight, or surface area [4].…”
Section: Discussionsupporting
confidence: 84%
“…The equation from that study, 4.98 + 0.1 55 x age (month), generally overestimates the renal length in our sample [2]. Two of the previous studies predicted renal volume, a more complicated measurement of kidney size than length [3,5]. This measurement is more cumbersome for the clinician and radiologist, and rather than deal with this cumbersome measurement, most sonographers ignore the standards.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Lotus and others made a similar observation of the independence of renal length of gender in their study conducted o Chinese children 9 , Komus and colleagues 20 , in their study on Turkish children and Adeyekum and colleagues also noted a similar trend, in Nigerian children 19 . The volume of kidney was also some what lowers than the others data which was 10cc 21 in comparisons to 9.79 to 9.82 cc in our series, but due to scanty information about the volume of term baby.…”
Section: Discussioncontrasting
confidence: 70%
“…Some studies found no difference [29,30], whereas others have suggested the left kidney to be larger [31,32]. Most consistent findings have been reported for kidney length, for which the left kidney seems to be longer than the right [7,25,26,31,33].…”
Section: Discussionmentioning
confidence: 79%